Population, economic development, and the environment - Lindahl-Kiessling, Kerstin, 1924-; Landberg, Hans. (Oxford ; New York : Oxford University Press, 1994)
Global population increase and production and consumption patterns and levels make the crucial issues first raised by Malthus two hundred years ago more important than ever. The position taken in this book is that the issues of population and its growth or decline cannot be separated from the whole set of questions of economic and social development, and from the environmental concerns related to the production and consumption of peoples throughout the whole of the world. Analysis must thus be made at the global, as well as at regional levels.
1. Population, Development, and Institutional Change: Summary and Analysis / Tommy Bengtsson and Christer Gunnarsson -- 2. The Environmental Resource Base and Human Welfare / Partha Dasgupta, Carl Folke and Karl-Goran Maler -- 3. Population and Reasoned Agency: Food, Fertility, and Economic Development / Amartya Sen -- 4. An Ecologist View of the Malthusian Conflict / C. S. Holling -- 5. 'Children are like young bamboo trees': Potentiality and Reproduction in Sub-Saharan Africa / Caroline Bledsoe -- 6. Economic Analysis of Fertility: Micro-Foundations and Aggregate Implications / Robert J. Willis -- 7. Government, Population, and Poverty: A 'Win-Win' Tale / Nancy Birdsall -- 8. Institutional Analysis of Fertility / Geoffrey McNicoll -- 9. The Relevance of Malthus for the Study of Mortality Today: Long-Run Influences on Health, Mortality, Labour Force Participation, and Population Growth / Robert Fogel.
Includes bibliographical references.
Keywords: Population -- Economic aspects; Population -- Environmental aspects; Population policy; Developing countries -- Population; Developing countries -- Population -- Economic aspects; Developing countries -- Population -- Environmental aspects; Developing countries -- Population policy; Developing countries -- Population; Developing countries -- Population -- Economic aspects; Developing countries -- Population -- Environmental aspects; Developing countries -- Population policy